Arthritis relief at your fingertips the complete self-care guide to easing aches and pains without drugs - Gach, Michael Reed (Piatkus Books, 1989)
This is a practical, self-help programme for all arthritis sufferers, combining the natural techniques of acupressure, massage and gentle yoga-stretching in daily exercises and routines. Each exercise is designed to stimulate a series of key acupressure points, and a 15-minute session, two or three times a day, should be all that is needed to relieve the pressure - and therefore the pain - in stiff joints, reducing and possibly eliminating the need for prescription drugs. Photographs, diagrams and useful examples help the reader identify the 12 acupressure points most important in the treatment of arthritis, and allows you to choose a routine to suit your lifestyle. It also differentiates between arthritis pain in different areas of the body, and so should allow you to create and control an acupressure programme to suit your specific needs.